PENDAMPINGAN BELAJAR PENDIDIKAN FORMAL SANTRI TAMAN PENDIDIKAN AL QUR’AN - Faza Khoirul Muna; Novi Andriani; Titis Rosowulan (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This community service program aims to address the difficulties in formal academic mentoring experienced by students (santri) of TPQ (Qur'anic Education Center) Roudlotul Athfal in Tidaran 1 Hamlet. The limited time available to parents, who predominantly work as farmers and laborers, created a gap between the demands of formal schooling and the necessary learning support at home. The methodology employed was the Asset Based Community Development (ABCD) approach, which began with a Focus Group Discussion (FGD) to identify community needs and aspirations. Using the ABCD framework, the hamlet's primary asset—its educated youth—was identified as the key solution. The resulting intervention was a structured tutoring program implemented under the auspices of TPQ Roudlotul Athfal, with a synchronized schedule designed not to interfere with religious study sessions. The program successfully provided intensive academic guidance, enhanced the students' knowledge and self-reliance, while simultaneously developing the teaching skills and sense of social responsibility among the local youth, which is crucial for the program's sustainability.